PENERAPAN ALGORITMA LEVENSHTEIN DISTANCE PADA SISTEM PENCARIAN DATA BUKU BERBASIS WEB - Yuyun Nia Daniati; Ismail Abdurrazzaq Zulkarnain; Khoiru Nurfitri (Universitas Muhammadiyah Ponorogo, 2022)
In the world of education today really need a search engine that makes it easier for students to search for information related to book data. One of them is in the library of SMP N 2 SOOKO, the process of finding the number and stock of books at SMP N 2 SOOKO can take a lot of money and time because it needs to be recorded manually. With this web-based search system, it can save costs and time because the process is carried out using a computer. This study aims to create a web-based book data search system that makes it easier for the SMP N 2 SOOKO library in the process of searching for the number and stock of books as well as in the archiving process. This search system uses the Levenshtein distance algorithm which is used to find the smallest string distance or distance, so that the book data entered into the search column displays results that are close to the keywords. For the data collection method using the method of observation and interviews. The tools used to describe this system model are in the form of flowcharts, context diagrams and level 1 DFD. The software used for design and implementation is XAMPP as a webserver, phpMySQL as a database and notepad++ as an editor for writing PHP and HTML files. The research shows that the search for book data using the single target formula is 75% and multi target is 87%.